Cone valued Lyapunov functions and Lipschitz stability of nonlinear systems of differential equations - Olusola Akinyele (International Journal of Mathematics and Mathematical Sciences)
We introduce a new comparison result which will be an important tool when we apply cone valued Lyapunov like functions. We also introduce new concepts of ϕ0-uniform Lipschitz stability and (λ,λ,ϕ0)-practical stability and employ our comparison result to carry out stability analysis of nonlinear systems. Our results are also applicable to nonlinear perturbed systems.